Pengaruh Produksi dan Nilai Tukar Rupiah Terhadap Volume Ekspor Cengkeh Indonesia Ke Singapura Periode 2012-2021 - Lia Pianti Lia Pianti; Muhammad As’ad Muhammad As’ad; Hermansyah Hermansyah Hermansyah (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the effect of production and the rupiah exchange rate on the volume of Indonesian clove exports to Singapore. This study uses secondary data with a time series from the period 2012-2021. The population in this study is all data on production, rupiah exchange rate, and volume of Indonesian clove exports to Singapore from 2012-2021. Sampling in this study used the saturated sample method in order to obtain a sample of 30 data samples. This study uses a quantitative approach with the type of explanatory research. The data analysis technique used in this study is descriptive analysis, simple linear regression analysis, multiple linear regression analysis, coefficient of determination, t test and F test with SPSS version 26 program. The result of this study indicates that there is a partially significant effect of production (X1) on the volume of Indonesian clove exports to Singapore (Y) of 60.6% and there is a partially significant effect on the value of the rupiah exchange rate (X2) against the volume of Indonesian clove exports to Singapore (Y) was 54.7%. From the results of the research conducted, it can be seen that simultaneously production (X1) and the rupiah exchange rate (X2) have a significant effect on the volume of Indonesian clove exports to Singapore (Y) of 63.3% and the remaining 36.7% is influenced by other variables which were not investigated in this study.